An in vitro study to optimise treatment of varicose veins with radiofrequency-induced thermo therapy. (February 2015) - Badham, George E; Strong, Sophie M; Whiteley, Mark S
Objective: To develop a reproducible method of using radiofrequency-induced thermotherapy with adequate thermal spread to ablate the whole vein wall in a truncal vein but avoiding carbonisation, device sticking and high impedance "cut outs" reducing interruptions during endovenous treatments. Methods: Porcine liver was treated with radiofrequency-induced thermotherapy under glass to allow measurements, observation and video recording. Powers of 6–20 W were used at varying pullback speeds to achieve linear endovenous energy densities of 18–100 J/cm. Thermal spread, carbonisation of treated tissue and high-impedance cut outs were recorded. Results: The currently recommended power settings of 18 and 20 W produced sub-optimal results. If pulled back at 3 s/cm to achieve linear endovenous energy densities around 60 J/cm, tissue carbonisation and high impedance cut outs occurred. When high powers and fast pullbacks of 1 s/cm were used, no carbonisation or cut outs occurred but thermal ablation of the liver model was below target due to reduced time for thermal conduction. Low powers (6–12 W) with slow pullbacks (6–12 s/cm) achieved target thermal ablation with minimal carbonisation and high impedance cut outs. Conclusions: Using low power (6 W) and a slow discontinuous pullback (6 s every 0.5 cm, in steps), we were able to achieve our target thermal ablation in the porcine liver model without carbonisation and high impedance cut outs. This suggests the currently recommended power levels could be reduced, reducing the need to remove the device to clean the electrodes during treatment while achieving target thermoablation of the treated tissue.